Suicide as a social dilemma: Evidence from Pakistan - Ahmed, Zubair; Bhati, Ilyas; Kausar, Rizwana (Advances in Social Sciences Research Journal, 2019)
Abstract Suicide is one of the major causes of death around the globe. It has become sensitive and imperative anthropological, psychological and public health issue which need to be tackled. The present paper provides an overview of the growing literature on suicide or more commonly known as “attempted suicide or completed suicide”. Suicidal attempts (and /or completed suicides) are increasing in urban and rural areas of Pakistan such as Karachi, Ghizer, and Hunza. The exact reasons are indefinite. This paper focuses on existing literature 1) the concept of suicide; 2) analyzes the existing consensus/figures of suicide in Pakistan; 3) analyzes the main determinants; 4) risk factors of suicide; 5) analyzes the modes of suicide discussed in the existing literature on suicides in Pakistan; and 6) offers literature gap and limitations of the evidences. It has revealed that the exact factors of socio-cultural and economical determinants of suicide in rural and urban areas were investigated paradoxically due to lack of meticulous quantitative and qualitative research. Majority studies focused on suicide in women but not even a single study focused on underlying factors of suicide in men. Further methodical studies are suggested at the community level. Keywords: evidence, Pakistan, social dilemma, suicide, women